The Representation of Baba-Nyonya Cuisine in the Context of Halal Tourism Industry in Malacca, Malaysia - Tuti Elfrida; Syafiq Akmal Sazali; Muhammad Nasirin Abu Bakar (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
Culinary becomes one of the fast growing industries along with the development of tourism. The Baba-Nyonya or Peranakan foods is one of Malacca's distinctive dishes as a form of acculturation of Chinese and Malaysian culture which presents to complement the diversity of attractions and services in the Malaysian tourism and hospitality industry. Several Baba-Nyonya restaurants are available in Malacca and most are located in Bandar Hilir, where the Peranakan community lived in the past. Baba-Nyonya restaurants emerge to have contribution to the development of Malaysia as Halal Tourism Destination. This research then finds a form of representation of Baba-Nyonya foods in an effort to provide halal products and services in Malacca, Malaysia. Through observation, interviews, and literature studies it is known that some restaurants are starting to change food menus from pork menus to pork-free menus. Although they do not hold halal certificates, they are categorized as Muslim-friendly Baba-Nyonya Restaurants and visited by Muslim customers. The restaurant does not have pork on its menu, but chicken, duck, seafood and vegetables. Also, there is one Baba-Nyonya restaurant who has obtained a halal kitchen certificate and a certificate of cleanliness application, so that it can be a reference in the Halal system and industry. The establishment of a halal assurance system can also be pursued in order to further enhance the confidence of Muslim customers of the Baba-Nyonya food products consumed.